Bright prospects in service sector - New Straits Times, (2008)
JOBS in restaurants hotels and the leisure business may have been ranked as among the worst-paying jobs in America in a survey by Forbes.com last year, but renowned services marketing guru Professor Christopher Lovelock reckons that the service sector is where the prospects are this year in Asia.